Moving beyond surgical excellence: a qualitative systematic review into the perspectives and experiences of children, adolescents, and adults living with a rare congenital craniofacial condition and their parents - Mariët Faasse; Hester M. van de Bovenkamp; Karolijn Dulfer; Virginie Kauffman; Ivana Marinac; Veronica Leonardi; Gareth Davies; Philippe Pakter; Jana Angelova; Karen Wilkinson-Bell; Lars Kölby; Marizela Kljajić (Journal of Plastic Surgery and Hand Surgery)
This qualitative systematic review aims to get a better understanding of what it means to live with a rare congenital craniofacial condition according to patients and their parents. Eight patient representatives provided input to this study. After a systematic search, 1,291 studies were screened and 32 qualitative and mixed methods articles (> 691 participants) were included. ENhancing Transparency in REporting the synthesis of Qualitative research (ENTREQ), Cochrane, and COnsolidated criteria for REporting Qualitative research (COREQ) checklists were used for reporting qualitative evidence synthesis and assessment of reporting of included studies. Studies predominantly included parents’ perspectives and used mixed samples of diagnosis and sometimes combined the parent and patient perspectives. The results sections of the articles were analyzed inductively using Thematic Synthesis (i.e. line-by-line coding, generating descriptive and analytical themes). Five analytical themes were identified that describe experiences and perspectives: (1) Healthcare experiences, (2) Raising and Growing up, (3) Development of character, (4) Physical impact of the condition, and (5) Social experiences. Underlying themes illustrate that the different aspects throughout life are intertwined, that relationships in all different domains play an important role in shaping perspectives, and that experiences may change over time. Furthermore, it demonstrates that living with a craniofacial condition and undergoing treatment is multifaceted and that the perspectives of patients and parents may differ. In conclusion, well-being and quality of life of patients and their parents are dependent on many different aspects, and surgeons and other healthcare professionals should tailor their skills, expertise, and support to individual-specific needs besides medical indications and move beyond surgical excellence.